Prevalence and Spatial Distribution of Sickle Cell Anaemia in Gondia District, Maharashtra, India - Ashish Suresh Gadwe (International Journal of Scientific Research in Science and Technology, 2026)
Sickle cell anaemia (SCA) is a significant hereditary hemoglobin disorder prevalent among tribal and socioeconomically disadvantaged populations in central India. The present study investigates the prevalence, demographic characteristics, and spatial distribution of sickle cell anaemia in Gondia district, Maharashtra, using a retrospective cross-sectional design based on secondary data collected from hospital records and government screening programs over a period of ten years (2013–2023). A total of 1,318,567 individuals were screened, revealing a prevalence of 0.08% for sickle cell disease (SS) and 0.85% for sickle cell trait (AS). Statistical analysis using the Chi-square test demonstrated significant associations between disease prevalence and age, gender, community, and geographic distribution (p < 0.05). The highest prevalence was observed in the 11–20 years age group and among Scheduled Castes and Scheduled Tribes. Spatial analysis indicated clustering of cases in Gondia, Arjuni Morgaon, and Sadak Arjuni blocks. The narrow confidence intervals indicate high precision of estimates. The findings highlight the presence of a substantial carrier pool, indicating a future risk of increased disease burden. The study emphasizes the need for targeted screening, genetic counselling, and community-based awareness programs to effectively control and manage sickle cell anaemia in high-risk regions.
Keywords: Sickle cell anaemia; Prevalence; Gondia district; Tribal population; Spatial distribution; Chi-square analysis; Genetic disorder; Public health